Tribological Investigation of HVOF Sprayed Coated Turbine Steel under Varied Operating Conditions. (2020) - Sharma, Mithlesh; Kumar Goyal, Deepak; Kaushal, Gagandeep
Abstract: In the present work, Cr3 C2 -25NiCr and WC-10Co-4Cr coatings were deposited on AISI304 turbine steel using HVOF-spray process. Performance of these HVOF-spray coated and bare turbines steel was investigated under varied conditions of slurry erosion. Slurry erosion resistance was premeditated by using a laboratory developed slurry erosion test rig. Phases, microstructure and eroded surface were characterized using SEM and XRD analysis. It was observed that HVOF-spray WC-10Co-4Cr coating had shown remarkable erosion resistant feature due to the presence of dense, well bonded structure along with higher hardness followed by Cr3 C2 -25NiCr coated steel and AISI 304 bare turbine steel. It was observed that under erosion condition, bare steel and Cr3 C2 -25NiCr coating exhibited ductile followed by brittle mechanisms respectively. Similarly degradation mechanism for WC-10Co-4Cr coating exhibited mainly ductile behaviour